2015
DOI: 10.3329/jbas.v39i1.23657
|View full text |Cite
|
Sign up to set email alerts
|

Physiological analysis of growth and yield of potato in relation to planting date

Abstract: Experiments on planting date on growth and yield of potato revealed that planting date had a significant effect on plant height, crop growth and yield. Higher leaf area index (LAI) was observed in case of optimum sowing date (16 Nov.) which resulted in higher total dry matter (TDM) production and ultimately gave higher yield. Delayed planting gave lower LAI, lower TDM and had adverse effect on tuber yield. No significant variation was observed in tuber yield due to interaction effect of variety and planting da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…4.). Our present findings were in agreement with Mahmud (2012) and Begum et al (2011), who reported similar decreasing trend of RGR in potato varieties and the highest RGR value was calculated at 30-40 DAP. According to Abbas (2011), the variation in the RGR in the respective varieties might be due to difference in temperature or weather during the crop seasons.…”
Section: Relative Growth Rate (Mg Gday -1 )supporting
confidence: 93%
“…4.). Our present findings were in agreement with Mahmud (2012) and Begum et al (2011), who reported similar decreasing trend of RGR in potato varieties and the highest RGR value was calculated at 30-40 DAP. According to Abbas (2011), the variation in the RGR in the respective varieties might be due to difference in temperature or weather during the crop seasons.…”
Section: Relative Growth Rate (Mg Gday -1 )supporting
confidence: 93%
“…In sub plot treatments, during 60-75 DAS significantly highest relative growth rate was observed from D , environmental conditions. Similar results were also reported by Begum et al (2015).…”
supporting
confidence: 92%
“…Depending on the irrigation system, water consumption efficiency in potato varies from 5.4 to 12 kg m −3 16 , 24 . Drip irrigation is one of the most effective methods and ranged from 6.3 to 8.6 kg m −3 (Sharma 2007) 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al (2010) 32 achieved higher yields using the same irrigation system (40–48 t ha −1 ), and potato tuber weight was reduced under the slight water stress. Potato reacts to stress when soil water tension exceeds 20 kPa 24 . In a study by Amer et al (2016) 33 potato tuber yield also decreased with the application of excessive irrigation, resulting in greater stress, increased vegetative growth and potential leaching of nutrients from the root zone.…”
Section: Resultsmentioning
confidence: 99%